POTENTIAL BANKRUPTCY WITH SYSTEMIC IMPACT DURING PANDEMIC - Ismanto Hadi Santoso; Sony Kristiyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The world economy condition was not in the best condition in 2019 until several years later. This is due to the Covid pandemic, which has forced several countries to take firm action in the form of limiting community activities as a whole, resulting in a decline in economic activity. Restrictions on community activities will result in a general economic downturn marked by a decline in economic growth. The banking business, which relies heavily on good economic conditions, will certainly be affected. The worst possibility that can happen is the bankruptcy of the bank caused by the pandemic. This study tries to reveal how the potential for bankruptcy may be experienced by the bank. The sample of this research is a group of banks with systemic impact in Indonesia based on the decision of the Financial Services Authority of the Republic of Indonesia in 2017. According to this decision, there are fifteen banks in Indonesia which are categorized as systemic impact banks. This study used fourteen banks and left one bank with a systemic impact due to insufficient data for processing. By using commonly used bankruptcy measures, this study concludes that in the period of observation, there are three banks that have the potential to go bankrupt and the rest are in the gray area and there is no bank that does not have the potential to go bankrupt.